Bacterial Contamination at Whiteleg Shrimp (Litopeanaeus vannamei) in Aquaculture - -, Mashuri Masri; Sukmawaty, Eka; Nur, Fatmawati; Suriani, Suriani (Jurnal Biodjati, 2021)
Indonesia hasÂ a very highÂ biodiversity, which has later become one of the natural products of interest to the international community,Â including fishery products.Â One of the high-demand Indonesian fishery products isÂ whiteleg shrimp Litopeaneus vannamei. However, safety food Exported whiteleg shrimp products must meet the criteria, includingÂ free from bacterial contamination such as Escherichia coli, Salmonella, Vibrio cholera. This study attempttedÂ to analyze E. coli, Salmonella, V. cholerae contamination in 3 ponds in Bojo, Cilellang, and Palanro Village in District Malusetasi, Barru Regency, South Sulawesi. Two samplings for each pond were conducted in the morningÂ were pond waterÂ and Â fresh whiteleg shrimp. SNI 2728-2018 specifies the quality and safety requirements for fresh shrimp. This standard applies to whole or headless fresh shrimp handled from fresh shrimp and does not apply to fresh shrimp that has undergone further processing. Based on SNI 2728-2018, the E. coli test showed positive in Cilellang VillageÂ (sample A) with 11 MPN/g, negative in Palanro Village (sample B) and in Bojo village (sample C) with the value of <2 MPN/g. Escherichia coli test showed positive in sample D (Vannamei shrimp in Cilellang Village) and sample E (Vannamei shrimp in Palanro Village) with 2.0 MPN/g, 17 MPN/g,Â respectively.Â Only sample F (Vannamei shrimp in Bojo village ) showed a negative result. As for the Salmonella test, positive results showed in sample A, while sample B and sample C showedÂ negativeÂ results. The Vibrio cholerae test showed negative at allÂ samples. . This study concludes that Whiteleg shrimp from ponds in Mallusetasi District is classified as safe for consumption.